Differences in the management of ruptured intracranial aneurysms: a survey of practice amongst British neurosurgeons. Issue 8 (August 1987) - Marsh, H; Maurice-Williams, R S; Lindsay, K W
Abstract : British consultant neurosurgeons in post for at least one year were sent a postal questionnaire about the way in which they managed patients with ruptured aneurysms; 87% replied. Wide differences were evident in almost all aspects of treatment, before, during and after surgery. A consensus of opinion appeared in only a few areas: the employment of magnification during surgery, the use of clipping as the preferred method of surgical treatment, and a general reluctance to operate on patients with a depressed conscious level within a week of haemorrhage.